Acute intermittent porphyria: characterization of a novel mutation in the structural gene for porphobilinogen deaminase. Demonstration of noncatalytic enzyme intermediates stabilized by bound substrate. - Desnick, R J (1985)
To investigate the molecular pathology in acute intermittent porphyria (AIP), the nature of the defective porphobilinogen (PBG)-deaminase was determined in erythrocyte lysates from 165 AIP heterozygotes from 92 unrelated families representing 20 different ethnic or demographic groups. Immunologic and physicokinetic studies revealed the occurrence of four classes of PBG-deaminase mutations. In the majority of families studied, the amount of immunoreactive enzyme protein corresponded to the amount of enzymatic activity, indicating the absence of cross-reacting immunologic material (CRIM) produced by the mutant allele. In 78 of these CRIM-negative families (designated type 1), the affected heterozygotes had half-normal PBG-deaminase activity. In three families (designated CRIM-negative type 2), symptomatic patients had increased urinary excretion of delta-aminolevulinic acid and PBG, and normal levels of erythrocyte PBG-deaminase activity. In contrast, noncatalytic, immunoreactive protein was expressed in heterozygotes from 11 families, about one-eighth of those studied, consistent with mutations in the structural gene for PBG-deaminase. Two types of CRIM-positive mutations were identified: the type 1 mutation had a CRIM/activity ratio of approximately 1.7 and a crossed-immunoelectrophoretic profile in which all the enzyme intermediates were increased, with the B or monopyrrole-enzyme intermediate predominant (B greater than A much greater than C congruent to D greater than E). The mutation altered both the kinetic and stability properties of the noncatalytic immunoreactive enzyme protein. The second CRIM-positive mutation, type 2, had markedly increased levels of noncatalytic immunoreactive protein (CRIM/activity ratio approximately 5.7). Crossed-immunoelectrophoresis revealed markedly increased amounts of the substrate-bound intermediates, B, C, D, and E (B greater than C greater than D greater than E much greater than A). The accumulation of these noncatalytic enzyme intermediates presumably resulted from the enhanced binding and/or defective release of substrate molecules. The conformation of these enzyme-substrate intermediates apparently rendered the complexes more resistant to intraerythrocyte proteolysis. These findings provide evidence for the presence of different allelic mutations in the structural gene for PBG-deaminase and document molecular genetic heterogeneity in AIP.